Komunikasi Kelompok Di Kalangan Komuter - Siti Khadijah; Djuara P Lubis; Rilus A Kinseng (Institut Pertanian Bogor, 2015)
The speed of urban development, has caused a very heavy commuter. This study aimed to analyze the relationship between the characteristics of the group members, with the process of communication and cohesiveness among commuters. The study was conducted to 86 members of the group in KA.Patas Purwakarta with quantitative methods using questionnaires as research instruments. Test analysis using Spearman rank statistic and chi Square to analyze the relationship between the characteristics of the group members, with the communication process and individual attitudes towards cohesiveness among commuters. The study states that the age of negative relationship with the communication process. The older the age of a member was, the lower the knowledge and the obedient of the group `s norm he had. Female members had a higher involvement in the communication process of the group than the male members. There was a negative relationship between the occupation and the cohesiveness of the group. The better occupation they had, the lower degree of cohesiveness they showed. There was a significant relationship between the sex of members and their cohesivenessoutside the railway coach. Cohesiveness was found having very significant relationship with the information accessKeywords: Group Communication, Cohesiveness, Commuter.